2020
DOI: 10.18553/jmcp.2020.26.12.1529
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the association between medication adherence, as defined in quality measures, and disease-state control, health care utilization, and costs in a retrospective database analysis of Medicare supplemental beneficiaries using statin medications

Abstract: Assessing the association between medication adherence, as defined in quality measures, and disease-state control, health care utilization, and costs in a retrospective database analysis of Medicare supplemental beneficiaries using statin medications 1530

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…An important study limitation is that beyond analysing PDC, our model did not assess the quality of care that patients with chronic hypertension received. Studies from a range of other specialties demonstrated that optimal longitudinal healthcare use may be associated with decreased risk 28,29 . These longitudinal care use models have not been translated to the obstetric population and the effect of care quality in accounting for risk is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important study limitation is that beyond analysing PDC, our model did not assess the quality of care that patients with chronic hypertension received. Studies from a range of other specialties demonstrated that optimal longitudinal healthcare use may be associated with decreased risk 28,29 . These longitudinal care use models have not been translated to the obstetric population and the effect of care quality in accounting for risk is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from a range of other specialties demonstrated that optimal longitudinal healthcare use may be associated with decreased risk. 28,29 These longitudinal care use models have not been translated to the obstetric population and the effect of care quality in accounting for risk is unknown. Second, our inclusion criteria may have disproportionately sampled Medicaid patients with higher comorbidity.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…На отечественном рынке можно выделить устройства фирмы BRADEX 4 каждая ячейка может вместить до 18 таблеток). Такая таблетница может быть удобна для использования в домашних условиях, но ее размер позволяет сделать предположение о статусе здоровья владельца.…”
Section: таблетницы и сумкиunclassified
“…Axon и соавт. [4] продемонстрировано, что соблюдение режима фармакотерапии (не менее 80% от общего числа приема ЛП) даже в течение 1 года снижало затраты на здравоохранение у пациентов, принимавших статины. Похожие исследования проводились для групп пациентов с сахарным диабетом [5] и гипертонией [6], во всех случаях было отмечено снижение общих расходов на лечение.…”
Section: Introductionunclassified
“… 6–8 A recent meta-analysis indicated that adherence to statins has been shown to improve outcomes and reduce health care cost. 9 Adherence to medication regimens has been associated with reduced hospitalization and health care costs in patients with chronic illnesses that include diabetes mellitus, hypercholesterolemia, hypertension, and congestive heart failure. 10 Maintaining adherence to medication regimens can be a challenge, especially in patients with a high pill burden.…”
Section: Introductionmentioning
confidence: 99%